PENINGKATAN HASIL BELAJAR KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS VIII-8 SMP N 6 BANDA ACEH MELALUI MODEL PEMBELAJARAN TIME TOKEN SEMESTER GANJIL TAHUN PELAJARAN 2015-2016 - Tirabidah, (Jurnal Serambi Ilmu, 2024)
The main aims of this research are to improve the students’ achievement, participation, motivation in English speaking skill, and also to improve the teacher’s competence in teaching learning proses for classroom menegement. The teaching model used in this research was Time Token teaching learning model. This action research was implemented in two cycles. Each cycle consisted of three meetings. The instruments used to gain the data are oral and written speaking skill test, observation, and questionnaire. The tests are used to see the students’English skill achievement in each teaching learning process, the observation is used to observe the teaching learning process, and the questionnaire is used to see the students’ responses toward teaching learning process through time token teaching learning model.The subjects of the reaserch are the students of class VIII-8. From data analysis showed the results that the students’ achievement improved from the first cycle 57% up to 80% in the second cycle. The students’ participation also improved from 50% in the first cycle up to 90% in the second cycle. The students’ motivation also improved from 62% in the first cycle up to 80% in the second cycle. Similarly, the teacher’s competence in teaching learning proses improved from 73% in the first cycle up to 88% in the second cycle.Based on the data above, it can be concluded that time token model can improve the students’ achievement, motivation, and participation in speaking English. Moreover, this model also can improve the teacher’s competence in teaching learning proses. And it is recomended that the teachers apply time token teaching learning model in teaching learning process.